2005
DOI: 10.1128/jvi.79.18.12058-12064.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Replication of Duck H5N1 Influenza Viruses in a Mammalian Mouse Model

Abstract: We recently analyzed a series of H5N1 viruses isolated from healthy ducks in southern China since 1999 and found that these viruses had progressively acquired the ability to replicate and cause disease in mice. In the present study, we explored the genetic basis of this change in host range by comparing two of the viruses that are genetically similar but differ in their ability to infect mice and have different pathogenicity in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
486
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 499 publications
(500 citation statements)
references
References 30 publications
(22 reference statements)
12
486
1
1
Order By: Relevance
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…Several amino acid changes in PB2 are important for the replication or virulence of influenza viruses in mammals (22)(23)(24)(25)(26)(27)(28)(29)(30). A detailed comparison of the amino acid differences among the EAH1N1 SIVs indicated that all of these viruses have mammalian-adapting mutations in their PB2 genes (SI Appendix, Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…As described (30), all eight Vic75 genes were amplified and cloned into a viral RNA (vRNA) expression plasmid, and Vic75 PB2, PB1, PA, and NP genes were cloned into an mRNA expression plasmid. All eight genes of HK486 were amplified from vRNA by RT-PCR with a One-Step RT-PCR kit (Qiagen, Valencia, CA) and cloned into a bidirectional plasmid (pBD) that possesses vRNA expression elements from pPolISapIRib (31,32) and mRNA expression elements from pCI (Promega, Madison, WI). Reassortant viruses were rescued as described (33) by using the 12-plasmid Vic75 system, the eight-plasmid HK486 system, or a combination of the two.…”
Section: Methodsmentioning
confidence: 99%
“…The 627K and 701N residues in the PB2 protein contribute to the replication and transmission of avian influenza viruses in mammalian hosts [11][12][13][14]. The three avian and environmental H7N9 viruses had the avian-like 627E residue.…”
Section: Molecular Signatures Of the Novel H7n9 Virusesmentioning
confidence: 99%